A Study on the Influencing Factors of Continued Intention to Use MOOCs: UTAUT Model and CCC Moderating Effect - Li, Yalin; Zhao, Min (Frontiers in Psychology, 2021)
Massive Open Online Courses (MOOCs) is the product of “internet + education”, which offer the open educational resources to global students. This paper analyzed the influencing factors of students continued intention to use MOOCs. To achieve research objectives this study integrates uniﬁed theory of acceptance and use of technology (UTAUT) and connected classroom climate (CCC). In this study, 312 valid samples were used to verify the hypothesis proposed with the help of structural equation modeling (SEM) and PROCESS. The results showed that the factors of UTAUT model (performance expectancy, effort expectancy, social influence and facilitating conditions) were significant positive effects on continued intention to use MOOCs. More importantly, there was a significant moderating effect of CCC between UTAUT and the continued intention to use MOOCs. Based on this research the findings, implications and limitations are discussed.